Comparison of Effectivenness Between Ibuprofen and Paracetamol in the Treatment of Fever in Children Aged 0-18 Years a Systematic Review and Meta-Analysis of Randomized Control Trials - Anggi Fibritiani (Yayasan Adra Karima Hubbi, 2023)
Fever is defined as one of the acute adaptive physiological responses to conditions caused by infection, characterized by an increase in body temperature ?38°C. Acetaminophen (paracetamol) and ibuprofen are the only two choices of over-the-counter drugs for the antipyretic class. Acetaminophen (paracetamol) and ibuprofen are the two over-the-counter drug choices, the only antipyretic class most often prescribed to treat fever in children. Acetaminophen (paracetamol) is considered the safest over-the-counter drug to control fever in children, while ibuprofen is a non-steroidal anti-inflammatory drug that works by inhibiting the synthesis of prostaglandin E2 in the anterior hypothalamus thereby reducing the temperature regulation center and can achieve a cooling effect. This made the authors interested in presenting a systematic review to compare the antipyretic profiles of acetaminophen with ibuprofen in the treatment of fever in children aged 0-18 years. Articles were searched through the database from January 2019 - January 2022. Searches were obtained from the PUBMED database. There was no attempt by the authors to specifically search for unpublished articles in English or Indonesian. Free full text or articles that can be downloaded for free (open access) articles with randomized controlled trials. The subjects used were children aged 0-18 years. Based on research results that ibuprofen is more effective than acetaminophen in treating fever in children. This was evidenced from the 8 articles discussed, 4 of which said that the use of ibuprofen was more effective in lowering body temperature, while 3 articles concluded that both were balanced and equally effective, while 1 other said that combination or alternating therapy resulted in more effectiveness than monotherapy in lowering body temperature. body temperature. However, the benefits appear to be small in comparison and may not be clinically relevant.